Results of aortic valvuloplasty in neonates with critical aortic stenosis - I. Chornenka; N. Rudenko; A. Maksimenko; I. Yemets (Ukrainian Journal of Cardiovascular Surgery, 2016)
The article discusses the results of treatment of critical aortic stenosis in 23 patients aged under 1 month. The main methods of treatment is commissurotomy. All operated patients survived. The follow-up is 23,4±15,5 months. Today the contractile ability of myocardium, in all patients, who are observed, is maintained (ejection fraction 68±1,7%), average aortic valve gradient 23±15,6. Freedom from re-operation in the remote period – 89,5% and survival – 90,5%. So surgical valvuloplasty is an effective treatment of aortic stenosis in the neonates with good immediate and remote results.